2002
DOI: 10.1104/pp.008045
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic and Other Phosphoenolpyruvate Carboxylase Isoforms in the Single-Cell, Facultative C4System of Hydrilla verticillata  

Abstract: The submersed monocot Hydrilla verticillata (L.f.) Royle is a facultative C 4 plant. It typically exhibits C 3 photosynthetic characteristics, but exposure to low [CO 2 ] induces a C 4 system in which the C 4 and Calvin cycles co-exist in the same cell and the initial fixation in the light is catalyzed by phosphoenolpyruvate carboxylase (PEPC). Three full-length cDNAs encoding PEPC were isolated from H. verticillata, two from leaves and one from root. The sequences were 95% to 99% identical and shared a 75% t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…However, genes putatively encoding all of the enzymes required for C 4 photosynthesis were identified (see Table 10). Whereas C 4 photosynthesis has yet to be unequivocally shown in unicellular organisms (24,25,37,38), C 4 in the absence of Kranz anatomy is now well documented, especially in Hydrilla verticillata, a facultative C 4 aquatic monocot (39). Unlike T. pseudonana, which appears to lack plastid-localized NADP-dependent malic enzymes (NADP-ME), O. tauri has two NADP-ME orthologs most similar to H. verticillata (40) with at least one apparently targeted to the chloroplast based on ChloroP and TargetP predictions.…”
Section: Resultsmentioning
confidence: 99%
“…However, genes putatively encoding all of the enzymes required for C 4 photosynthesis were identified (see Table 10). Whereas C 4 photosynthesis has yet to be unequivocally shown in unicellular organisms (24,25,37,38), C 4 in the absence of Kranz anatomy is now well documented, especially in Hydrilla verticillata, a facultative C 4 aquatic monocot (39). Unlike T. pseudonana, which appears to lack plastid-localized NADP-dependent malic enzymes (NADP-ME), O. tauri has two NADP-ME orthologs most similar to H. verticillata (40) with at least one apparently targeted to the chloroplast based on ChloroP and TargetP predictions.…”
Section: Resultsmentioning
confidence: 99%
“…This was followed by a very detailed analysis of the single-cell C 4 metabolism in H. verticillata including studies of the biochemical pathways, enzymes and molecular genetics and its relationship to the acid-base polarity of leaf surfaces Magnin et al, 1997;van Ginkel et al, 2001;Rao et al, 2002Rao et al, , 2006aRao et al, , 2006bRao et al, , 2008Estavillo et al, 2007). Reiskind et al (1988) and Reiskind and Bowes (1991) demonstrated C 4 biochemistry in photosynthesis of the one ulvophycean green macroalga, Udotea flabellum, but not in another, Codium decorticatum.…”
Section: Introductionmentioning
confidence: 98%
“…verticillata is an aquatic macrophyte that can shift from C 3 to C 4 photosynthesis under low CO 2 conditions, without its leaf cells undergoing any structural modifications (Rao et al, 2006a;Rao et al, 2002;Estavillo et al, 2007). During this transition, genes encoding C 4 -specific isozymes of phosphoenolpyruvate carboxylase (PEPC), pyruvate orthophosphate dikinase (PPDK), NADP-malic enzyme (NADP-ME) and carbonic anhydrase (CA) are up-regulated (Rao et al, 2006a;Rao et al, 2002;Estavillo et al, 2007;Brautigam et al, 2014;Reiskind and Maberly, 2014). In H. verticillata there are three isoforms of PEPC, of which only one isoform is up regulated in C 4 leaves and has C 4 -like isoform kinetics (Rao et al, 2008).…”
Section: Introductionmentioning
confidence: 99%